2001
DOI: 10.1046/j.1365-2273.1999.00190.x
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-four hour ambulatory nasal pH monitoring

Abstract: The nasal delivery of drugs, both for systemic and local use, is an expanding field with many drugs being delivered by this route. It is known that changes in pH can affect drug absorption but there is no data regarding intranasal pH over time. We present the results of 24-h ambulatory nasal pH monitoring in four subjects, each of whom had monitoring on two separate occasions. The apparatus consisted of a pH monitor with two electrodes, thus enabling us to take readings from 1 and 4 cm behind the anterior end … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 5 publications
1
23
0
Order By: Relevance
“…Thus potentially, alterations in airway surface pH may explain many of the phenotypic hallmarks of CF and may lead to new treatment options. Airway surface pH has been previously measured in the nose, and both the equipment and methodology are well established [23,24]. Previous studies have reported that nasal pH varies with race [25] and the presence of rhinitis [26].…”
mentioning
confidence: 99%
“…Thus potentially, alterations in airway surface pH may explain many of the phenotypic hallmarks of CF and may lead to new treatment options. Airway surface pH has been previously measured in the nose, and both the equipment and methodology are well established [23,24]. Previous studies have reported that nasal pH varies with race [25] and the presence of rhinitis [26].…”
mentioning
confidence: 99%
“…To assess the consequence of pH on the integrity of nasal mucosal surface, drug solutions of different pH values ranging from 2 to 12 were applied to rat nasal mucosa whose pH is 7.39 and the outcomes verified that when pH ranged from 3 to 10, negligible magnitude of proteins and enzymes were released from cells, indicative of no cellular damages. On the other hand, if pH values were lower than 3 or higher than 10, damages were observed intracellularly and at membrane level (Costantino et al, 2007;Hehar et al, 1999;Litvyakova & Baraniuk, 2001). …”
Section: Phmentioning
confidence: 99%
“…The degree of acidification of these surfaces in mammals varies depending on the distribution and activity of the submucosal glands. The pH of the human passageway has a range from 5.2 to 8.0 [13][14][15][16][17][18]. Therefore, the efficient infection of human URT cells requires a certain level of virus stability to acidic pH.…”
Section: Differences Between Human and Avian Influenza Virusesmentioning
confidence: 99%